The social and cultural history of Palestine : essays in honour of Salim Tamari - Tamārī, Salīm; Irving, Sarah (Edinburgh University Press, 2023)
"Over the past decade, histories of Late Ottoman and especially Mandate Palestine have moved away from the political framing of the Arab-Israeli conflict to consider questions of social and cultural history, as well as, increasingly, adopting new frameworks such as environmental and medical history. One of the most important voices in this movement, as a scholar and as a mentor of others’ work, has been Salim Tamari. This volume brings together both new and established researchers on Late Ottoman and Mandate-era social and cultural history, many of them Palestinian, to showcase the kind of work inspired by Tamari’s legacy, to reflect on the development of these themes in the historiographical context, and to contribute to the decolonisation of Palestinian history. The contents range from considerations of tourist souvenirs and artisanal manufacture to the social history of Gaza, and from debates around cosmopolitanism in colonial Palestine to the socio-economic roles of Palestinian women."--Provided by publisher.